Iridoid Compound 10-O-trans-p-Coumaroylcatalpol Extends Longevity and Reduces Alpha Synuclein Aggregation in Caenorhabditis elegans - Shukla, Virendra; C. Phulara, Suresh; Yadav, Deepti; Tiwari, Sudeep; Kaur, Supinder; M. Gupta, M.; Nazir, Aamir; Pandey, Rakesh (CNS & Neurological Disorders - Drug Targets, 2012)
Aging, the major cause of several ailments has led to intense exploration of potential drugs that delay aging and its associated effects. We mined the information on traditional Indian medicines and identified an iridoid, 10-O-trans-p- Coumaroylcatalpol (OCC), a major ingredient of Premna integrifolia Linn. (syn: Premna serratifolia). OCC forms an important constituent of famous herbal formulation ‘‘Dashmula’’, a ten herb formulation, commonly used for its various medicinal properties. Employing model system C. elegans, the effect of OCC on life span, stress resistance, chemotaxis, the content of reactive oxygen species (ROS) and on the aggregation of alpha synuclein was studied. OCC extended the mean life span of nematodes, increased their tolerance against chemical induced stress, improved the chemotaxis index and reduced the ROS content. Further, the aggregation of Parkinson's disease (PD) associated protein, alpha synuclein (asyn), was decreased when transgenic a-syn expressing worms were raised on OCC mixed diet. We extended the studies further to explore the possible genetic mechanism that mediates the observed effects of OCC. Employing the genetic knockout mutants TK22 [mev-1(kn1)III]; GR1307 [daf-16(mgDf50)I]; VC199 [sir-2.1(ok434)IV] and transgenic GFP expressing strain TJ356 [zls356; DAF-16::GFP], our studies revealed that the effects were mediated by daf-16 and not by sir-2.1 or mev-1. Our results indicate that OCC has the ability to ameliorate a-syn aggregation, reduce oxidative stress and promote longevity in C. elegans via activation of longevity promoting transcription factor DAF-16. Thus, OCC may serve as a lead compound of plant origin for important nutraceutical intervention against aging and age associated PD.
Keywords: aging